A novel truncated fusion gene ETV6::AC010198.2 in post-MPN acute myeloid leukemia caused by del(12)(p13p11) - Jiao Lu; Jiao Lu; Guanqun Yang; Qiurong Zhang; Man Wang; Man Wang; Lijun Wang; Lijun Wang; Lu Chen; Haoyue Chen; Xin Jiang; Chunhua Liu; et al. (Frontiers in Oncology)
The gene ETV6 has been confirmed to be a genetic susceptibility gene for thrombocytopenia and leukemia. Here, we report a long-chain noncoding RNA AC010198.2 as a novel fusion partner of ETV6, showing a karyotype of del(12)(p13p11), with poor prognosis in a post-MPN AML that has never been reported, which may be an vital initial event in the transformation of MPN to AML and deterioration of disease.